EXPLORING DIGITAL LEARNING TOOLS AS A MECHANISM OF PROMOTING STUDENTS' COLLABORATIVE WRITING IN HIGHER EDUCATION (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2024)
Collaborative writing (CW) has gained prominence in higher education as a mode of computer-supported collaborative learning. However, sustaining active engagement during collaborative writing processes remains a challenge. This research investigates the role of digital learning tools as a mechanism for promoting students' collaborative writing in higher education. The study included ninety-six (n=96) undergraduates from a public higher education institution in River State. The study adopted a quasi-experimental pre-test and post-test method. The results showed that wiki considerably improved students' writing skills. It was also discovered that the web application offers elements that promote collaborative learning among users. The result has implications for the development of effective writing in education.